App-based oral health promotion interventions on modifiable risk factors associated with early childhood caries: A systematic review - Ajay, Kamalapriya; Azevedo, Liane B.; Haste, Anna; Morris, Alexander John; Giles, Emma; Gopu, Banu Preethi; Subramanian, Murali Perumbakkam; Zohoori, Fatemeh Vida (Frontiers in Oral Health, 2023)
Background: Early childhood caries (ECC) is a preventable chronic disease. Parents’ knowledge and attitudes toward oral healthcare have been associated with higher caries experience in their children. Mobile apps within the context of mHealth interventions are a potential tool for raising awareness and informing parents about their children’s oral health. Objectives: The aim of this systematic review was to examine the effectiveness of mobile health apps, targeted at parents and caregivers, for prevention of ECC. Data Sources: A systematic search was carried out in five scientific databases; Embase, CINAHL, MEDLINE, PsycInfo and Web of Science. Study Selection and Data Extraction: Original studies, delivering oral health interventions to parents of children <6 years via smartphones, were included. Both quantitative and qualitative findings from the included studies were extracted. Synthesis: A convergent segregated approach was used to integrate the quantitative and qualitative evidence, followed by side-by-side display and narrative synthesis. Results: Out of 5,953 retrieved articles, five met the inclusion criteria and were included in the review. Three articles reported quantitative findings, while two reported both quantitative and qualitative findings. Four studies reported that a mobile app can be an effective tool to improve the oral health knowledge of parents/caregivers, aiding them in incorporating good oral health habits into their children’s daily routines. Conclusion: This review demonstrated that oral health promotion programs delivered through mobile apps to parents could be effective in improving child oral health awareness among parents. There is a need for more high-quality studies with large number of participants to find out which features of mHealth interventions with parents could effectively be employed to reduce the prevalence of ECC. Further studies and apps should be developed based on evidence-based behaviour change techniques and incorporate features such as gamification to increase effectiveness and engagement of the target population.